Taming Tibet : Landscape Transformation and the Gift of Chinese Development - Yeh, Emily T. (Emily Ting) (Book collections on Project MUSE., 2013)
"The violent protests in Lhasa in 2008 against Chinese rule were met by disbelief and anger on the part of Chinese citizens and state authorities, perplexed by Tibetans' apparent ingratitude for the generous provision of development. In Taming Tibet, Emily T. Yeh examines how Chinese development projects in Tibet served to consolidate state space and power. The master narrative of the PRC stresses generosity: the state and Han migrants selflessly provide development to the supposedly backward Tibetans, raising the living standards of the Han's "little brothers." Arguing that development is in this context a form of "indebtedness engineering," Yeh depicts development as a hegemonic project that simultaneously recruits Tibetans to participate in their own marginalization while entrapping them in gratitude to the Chinese state. The resulting transformations of the material landscape advance the project of state territorialization. Exploring the complexity of the Tibetan response to--and negotiations with--development, Taming Tibet focuses on three key aspects of China's modernization: agrarian change, Chinese migration, and urbanization"--